2007
DOI: 10.4028/www.scientific.net/msf.546-549.183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Al-Sr Master Alloys on the As-Cast Microstructure of the AZ31 Magnesium Alloys

Abstract: The influence of Al-10.5%Sr master alloy, which is much cheaper than Mg-Sr master alloys, on the as-cast microstructure of the AZ31 alloy was investigated. The research results revealed that the Al-10.5%Sr master alloy produced obvious modification of the as-cast microstructure of the AZ31 alloy, and the modification efficiency increased with the holding time from 0min to 60min and the amount of Sr from 0.01% to 0.1%. Moreover, the results also showed that the Al-10.5%Sr master alloys of different states had d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…For example, Srinivasan et al and Nam et al [8,9] reported the addition of Al-10Sr master alloy to a Si-containing AZ91-Mg alloy appeared to refine the microstructure, and similar results were obtained in AM50-Mg alloy and AZ91-Mg alloy by Zhao et al and Hirai et al,respectively [10,11]. In addition, Zeng et al and Chen et al [12,13], respectively, reported that adding pure Sr or Al-10Sr alloy to AZ31-Mg alloy effectively reduced its grain size, and similar results were reported by other researchers [5,6].…”
Section: Introductionsupporting
confidence: 59%
“…For example, Srinivasan et al and Nam et al [8,9] reported the addition of Al-10Sr master alloy to a Si-containing AZ91-Mg alloy appeared to refine the microstructure, and similar results were obtained in AM50-Mg alloy and AZ91-Mg alloy by Zhao et al and Hirai et al,respectively [10,11]. In addition, Zeng et al and Chen et al [12,13], respectively, reported that adding pure Sr or Al-10Sr alloy to AZ31-Mg alloy effectively reduced its grain size, and similar results were reported by other researchers [5,6].…”
Section: Introductionsupporting
confidence: 59%
“…Considering that the mechanisms for grain refinement of the Sn or Sr containing Mg-Al based alloys have been described in detail in Refs. [15][16][17][18][19][20][21][22], and that the present work mainly focuses on the modification and refinement of the Mg 2 Si phase, therefore, the effects of Sr and Sn additions on the grain refinement of the Mg-6Al-1Zn-0?7Si alloy need not be discussed in this article.…”
Section: Resultsmentioning
confidence: 99%
“…Chen and co-workers [32] found that the effects of Al-Sr and Mg-Sr master alloys with different states on the refinement to magnesium alloys were very obvious. For example, the refinement efficiency of Mg-10Sr master alloy to AZ31 alloy was higher than that of the Al-10Sr master alloy (Fig.…”
Section: Effects Of Minor Sr On the Microstructure And Properties Of ...mentioning
confidence: 99%